Dermatofibrosarcoma protuberans – a wolf in sheep’s clothing: a case report and review of the literature - Ahsan, Mohammad Kamrul; Islam, Md Rashedul (BIRDEM Medical Journal, 2021)
Dermatofibrosarcoma protuberans (DFSP) is a locally invasive and slow growing tumor of the subcutaneous tissue. It rarely metastasizes but progressive and recurs frequently after surgical excision. The trunk and proximal extremities are the most common sites of the disease. A 53-year-old woman presented to dermatology outpatient department with a 3-cm, firm, violaceous and multinodular mass located on the left upper shoulder. Diagnostic work-up including magnetic resonance imaging and histopathological findings of biopsy were consistent with DFSP. The patient underwent wide local excision with skin flap reconstruction. No recurrence has been observed during ten months of follow-up. BIRDEM Med J 2021; 11(3): 246-249